A new paradigm for the regulation of the mammalian ribosomal RNA genes. (25th October 2006) - Moss, T.; Stefanovsky, V.; Langlois, F.; Gagnon-Kugler, T.
Abstract : Ribosome assembly occurs co-transcriptionally on the rRNA genes. This process requires the co-ordinated expression and assembly of many hundreds of proteins and is finely tuned to cell and organism growth. Co-ordinate regulation of the rRNA genes and the ribosomal protein genes is therefore essential for high-fidelity ribosome assembly. Recent work shows that rRNA gene transcription is regulated at the level of elongation via the mitogen-activated protein kinase pathway. We argue that this may provide an explanation for the high fidelity of ribosome assembly.